GROWTH AND PHOTOSYNTHETIC RESPONSES OF LONG BEAN (Vigna unguiculata) AND MUNG BEAN (Vigna radiata) RESPONSE TO FERTILIZATION - H. Nursu’aidah; M.R. Motior; A.M. Nazia; M.A. Islam (Journal of Animal and Plant Sciences, 2014)
Long bean (Vigna unguiculata)and mung bean (Vigna radiata) response to fertilization was studied through greenhouse experiments conducted at University of Malaya during 2011-2012. Long bean grown with fertilizer obtained the highest total chlorophyll (2.99 mg g-1), chlorophyll a (2.25 mg g-1), photosynthesis rate (1.26 µmol m-2 s-1) and identical total dry matter (31.54 g plant-1). Mung bean grown without fertilizer possessed the highest chlorophyll b (0.80 mg g-1) and chlorophyll a/bratio (0.62 mg g-1). Both long bean and mung bean grown without fertilizer produced the highest number of nodules and number of pods per plant. Fertilizer application had no significant response on seeds per pod, 100-seed weight and seed yield per plant for both crops. The results revealed that greater nodulation, higher pods per plant and identical seed yield can be a good indicator to avoid use of chemical fertilizer for both crops production in tropical Malaysia.
Keywords: Photosynthetic pigments; nodule; dry matter